Control de malezas mediante el uso de herbicidas preemergentes en el cultivo de arroz (Oryza sativa L.), bajo riego, en la zona de Babahoyo. - González Jiménez, Ruthbel Omar (2019)
VII. SUMMARY The present experimental work was carried out at the Palmar Farm of the Technical University of Babahoyo, within the area of the CEDEGE Project, province of Los Ríos. Located at Km 12 of the Babahoyo - Montalvo highway; at the UTM geographic coordinates: X = 672,825 Y = 9797,175; at 9 msnm. The annual average of precipitation is 2329.8 mm; 82% relative humidity; 998.2 hours of heliophany and temperature of 25.6 ° C Rice seed of the Iniap 15 variety was used as a genetic material. Seeds of rice of the variety INIAP-FL1480 were used as seed genetic material. The treatments of the STOMP® herbicides AQUA, BUTANOX, PELÍON in different doses were evaluated. The design that was used in the present investigation was of Completely Random Blocks (DBCA), with three treatments and three repetitions plus one witness. Comparisons of treatment measures were made using the Tukey test at 5% probability. All the practices and agricultural work that the crops needed for its normal development were carried out, such as land preparation, preparation of the nursery, sowing by transplant, weed control, irrigation, fertilization, phytosanitary control, weeding and harvesting. The data evaluated were toxicity index at 7 and 14 days after application; effectiveness of herbicides at 10, 20, 30 and 45 days; height of the plant; number of tillers and panicles / m² ; length of the panicles; grain by panicles; weight of 1000 grains; crop yield and economic analysis. Once the results were obtained, it was determined that the PELEON application caused the highest toxicity index at 7 and 14 with 2.67 equivalents to moderate damage, while the other treatments did not present phytotoxicity. In the control of weeds, the ranges ranged between 62 and 92% in the evaluations at 10, 20, 30 and 40 days, qualifying the applications of the products as good or very good for being within that range; the applications of STOMP® AQUA in 4 L doses had the best control percentages while the application of Pelíon in 2 liter doses had the highest percentages of weeds. In the application of STOMP® AQUA in a 4 L dose, it obtained the highest plant height, the highest number of tillers and panicles / m², the longest panicle length, the largest number of grains, the weight of the 1000 grains and yield presented in the applications of STOMP® AQUA in doses of 3 and 4 L. In the economic analysis it obtained profitable benefits, standing out the application of STOMP® AQUA, in a dose of 3 L with a net profit of $ 880.39. Keywords: weeds, herbicide, pre-emergent, irrigation.